Work–Family Conflict, Organizational Identification, and Professional Identification Among Chinese Nurses From a Resource Perspective. Issue 5 (2nd September 2022) - YANG, Chunjiang; CHEN, Aobo; SHENG, Nan
ABSTRACT: Background: The miserable work conditions faced by many nurses around the world make them particularly prone to work–family conflict. Purpose: This study was designed to explain from a resource perspective how and when nurses experiencing work–family conflict are more likely to exhibit decreased levels of organizational identification and professional identification. Methods: A time-separation research design was used, and data were collected from 322 nurses in five hospitals in China. All of the hypotheses were tested using conduct structural equation modeling. Results: The results showed that work–family conflict had negative effects on organizational identification and professional identification via emotional exhaustion. In addition, job meaningfulness may have a buffering effect on the negative impact of work–family conflict on emotional exhaustion, organizational identification, and professional identification. Conclusions/Implications for Practice: The results advance knowledge on how and when work–family conflict damages organizational identification and professional identification. Providing family support, relieving emotional exhaustion, and enhancing job meaningfulness are necessary to support the organizational and professional identification of nurses.